Investigating the effects of contaminants on the performance of oil based invert emulsion drilling fluid (2014)
Drilling fluid optimization is the main focus while drilling, this entails ensuring the fluid is at its right condition downhole at all time during drilling operation. The composition, including all additives added to the fluid must key into achieving the foremost goal of fluid optimization. Maintaining the integrity of drilling fluids downhole has become herculean especially at HTHP conditions. The possibility of fluid contamination at such prevalent downhole condition poses another major challenge to the fate of the drilling fluid. This work was undertaken to investigate the effect of clay and sea water (containing calcium and magnesium ions) contaminations on the rheology of the oil based invert emulsion fluid. Barite (Ba2SO4) was used as the weighting agent; the based fluid used for the oil based invert emulsion system was EDC-99, a specialized kind different from the conventional diesel oil. The fluid were analysed before and after aging using, rheometer, filtration and emulsion stability tests. From the experimental result, it was discovered that addition of contaminants lowered the electrical stability of the invert emulsion fluid. Fluid loss, Plastic viscosity, yield point and gel strength increased in the presence of contaminants. Only the plastic viscosity of the invert emulsion fluid was slightly out of API range for each set of contaminations, but this is still within the tolerance limit of an invert emulsion fluid with a S.G less than 1.61[1]. Fluid Rheology stabilization after HT aging indicate the suitability of the fluid to be employed for downhole HTHP drilling that may take longer time.